Creating "Community"? Preparing for Bushfire in Rural Victoria1. (21st February 2013) - Fairbrother, Peter; Tyler, Meagan; Hart, Alison; Mees, Bernard; Phillips, Richard; Stratford, Julie; Toh, Keith
Abstract: The term "community" has a long and contested lineage in social analysis and debate. This lineage, however, is not generally recognized in policy and public debates on community and bushfire in Australia. "Community" is thought to be central to bushfire preparedness in Australia, especially in rural areas, but what "community" actually means in this context is vague at best. There is an ever‐present tension between the use of "community" as a reference to locality, a "sense of community" as experienced by residents, and the use of "community" as a rhetorical tool by governments and state agencies. We argue that a rigorous analysis of the concept of "community" is critical to an understanding of the processes involved in preparing for the challenges associated with disaster, in this case bushfires. These broader issues are supported by research (a series of surveys, interviews, and focus groups) carried out with residents living in (predominantly rural) bushfire‐prone areas in the state of Victoria, Australia. Ultimately, we assert that social participation and social networks are likely to be the crucial aspects of community that play a central role in effective bushfire preparedness.